Administrativní budova - Pospíšil, David (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Moje diplomová práce řeší administrativní budovu. Budova se bude nacházet ve městě Šumperk. Bude situována nedaleko centra. Budova má dvě nadzemní podlaží a jedno částečně podsklepené podlaží. Stropy tvoří nosníky s keramickými vložkami a železobetonové desky. Svislé konstrukce tvoří keramické tvárnice v nadzemní části a betonové tvarovky v podzemní části. Střecha je, pochozí, vegetační. Schodiště je železobetonové, monolitické. Celý objekt je zateplen minerální vatou. Suterén je zateplen pěnovým polystyrenem.

My thesis solveses the office building. The building will be located in Šumperk. It will be located near the center. The building has two floors and a partial basement floor. Ceilings are beams with ceramic inserts and reinforced concrete slabs. Vertical structure consists of a ceramic blocks in the aboveground parts and concrete blocks in the underground section. The roof is walked on vegetation. The staircase is reinforced concrete, monolithic. The entire building is insulated with mineral wool. Basement is insulated with polystyrene foam.
Office Building
Keywords: Administrativní budova; strop; nosník; keramická vložka; železobeton; deska; tvárnice; beton; vegetační; monolitické; suterén; minerální vata; pěnový polystyren; Office building; ceiling; beam; ceramic insert; reinforced concrete; slab; block; concrete; vegetation; monolithic; basement; mineral wool; polystyrene foam